Does HIV Pre-Exposure Prophylaxis Modify the Effect of Partnership Characteristics on Condom Use? A Cross-Sectional Study of Sexual Partnerships Among Men Who Have Sex with Men in San Francisco, California - Prescott, Maximo R. (AIDS Patient Care STDS, 2019)
Increasing rates of sexually transmitted infections (STIs) in the United States among men who have sex with men (MSM) have raised concerns that pre-exposure prophylaxis (PrEP) has been associated with higher engagement in condomless anal intercourse (CAI). While partnership characteristics have previously been found to influence condom use, the extent to which PrEP use may modify their effect on CAI remains unknown. A secondary analysis of 535 sexual partnerships from a cross-sectional study in San Francisco was conducted to evaluate interactions between PrEP use and partnership characteristics on CAI. Bivariate and multivariate generalized estimating equation (GEE) logistic regression models were used to estimate relative measures of association, adjusted for confounding by seroconcordance and partnership type, as well as account for repeated partnerships per respondent. Partnerships where both partners used biomedical prevention had significantly greater odds of CAI [odds ratio (OR) = 5.19, 95% confidence interval (CI): 2.27–11.9] compared to those where only one partner used biomedical prevention, while those where neither partner used biomedical prevention had significantly lower odds of CAI (OR = 0.61, 95% CI: 0.40–0.93). There was no significant association between meeting place (online vs. offline) and sexual risk taking (OR = 1.03, p = 0.894). Having one partner disclose their HIV status (compared to neither partner having disclosed) was associated with significantly higher odds of CAI among partnerships of PrEP-using MSM [adjusted OR (aOR) = 5.28, 95% CI: 1.91–14.61], while the association was not significant among the partnerships of non-PrEP-using MSM (aOR = 1.29, 95% CI: 0.75–2.21). Differences in condom use among MSM using PrEP may not be well explained by differences in the effect of partnership characteristics. MSM using PrEP appear to commonly practice biomedical matching and high engagement in CAI with other biomedical prevention users, which could indicate relatively concentrated sexual networks and partly explain their disproportionate risk for STIs. Future studies should further investigate biomedical matching to develop interventions that further promote the sexual health of those using PrEP.